Influence of bone drilling parameters on the thermal stress distribution - Fernandes, M.G.A. (2017)
The material removal through the drilling involves two important processes. The first one is the drilling of material by cutting edges of the drill bit and the second is the friction generated by the contact between the drill bit and the hole wall of the material. Both processes lead to heat generation during drilling. In clinical practice, drilling procedures with high-speed cutting tools are often applied on bone tissue. These operations are associated to complications such as thermal osteonecrosis due to the excessive heat generation and mechanical damage due to the excessive levels of penetration force. The development of additional tools for accurately simulate the drilling is essential to predict the risk of thermomechanical damage during bone drilling. This paper investigates the thermal and mechanical damage in bone tissue induced by different parameters. An experimental and numerical approach of bone drilling has been conducted. A three-dimensional dynamic numerical model was developed to predict the thermo-mechanical stress generated during the drilling. The numerical model incorporates the geometric and dynamic characteristics involved in the drilling processes, as well the developed temperature inside the material. The numerical analysis has been validated by experimental tests using polyurethane foam materials with similar mechanical properties to the human bone.